Video-Assisted Palatopharyngeal Surgery: A Model for Improved Education and Training. (September 2014) - Allori, Alexander C.; Marcus, Jeffrey R.; Daluvoy, Sanjay; Bond, Jennifer
Objective: The learning process for intraoral procedures is arguably more difficult than for other surgical procedures because of the assistant's severely limited visibility. Consequently, trainees may not be able to adequately see and follow all steps of the procedure, and attending surgeons may be less willing to entrust trainees with critical portions of the procedure. In this report, we propose a video-assisted approach to intraoral procedures that improves lighting, visibility, and potential for effective education and training. Design: Technical report (idea/innovation). Setting: Tertiary referral hospital. Patients: Children with cleft palate and velopharyngeal insufficiency requiring surgery. Interventions: Video-assisted palatoplasty, sphincteroplasty, and pharyngoplasty. Main Outcome Measures: Qualitative and semiquantitative educational outcomes, including learner perception regarding "real-time" (video-assisted surgery) and "non–real-time" (video-library–based) surgical education. Results: Trainees were strongly in favor of the video-assisted modality in "real-time" surgical training. Senior trainees identified more opportunities in which they had been safely entrusted to perform critical portions of the procedure, corresponding with satisfaction with the learning process scores, and they showed greater comfort/confidence scores related to performing the procedure under supervision and alone. Conclusions: Adoption of the video-assisted approach can be expected to markedly improve the learning curve for surgeons in training. This is now standard practice at our institution. We are presently conducting a full educational technology assessment to better characterize the effect on knowledge acquisition and technical improvement.